Social concertation in times of austerity. European integration and the politics of labour market reforms in Austria and Switzerland - Afonso, Alexandre (Amsterdam, 2013)
"A term specifically found in European politics, social concertation refers to cooperation between trade unions, governments and employers in public policy-making. Social Concertation in Times of Austerity investigates the political underpinnings of social concertation in the context of European integration. Alexandre Afonso focuses on the regulation of labor mobility and unemployment protection in Austria and Switzerland, two of Europe’s most prosperous countries, and he looks at nonpartisan policymaking as a strategy for compromise. With this smart, new study, Afonso powerfully enters the debate on the need for a shared social agenda in post-crisis Western Europe."